EVOLUTION FEATURES OF GIANT SOURCES WITH LINEAR AND BREAK STEEP RADIO SPECTRA - Miroshnichenko, A. P. (Одеські астрономічні публікації, 2017)
In the framework of the cosmological model CDM the features of properties of giant radio sources with steep low-frequency spectra of linear (S) and break (C+) types are examined. Our estimates of characteristic age of galaxies and quasars with steep spectrum from the UTR-2 catalogue have values 107-108 years. We consider that steep radio spectra may be formed at the transient injection by synchrotron losses of relativistic electrons. Earlier we have determined two evolution branches in relation of the characteristic age and ratio of emission of torus and accretion disk crown for sources with steep spectra S and C+. To further examination of evolution features of giant sources with steep spectra we consider ratio of emission of radio lobes and accretion disk (and disk crown) versus velocity of jet propagation and characteristic age of these objects. Analysis of ob-tained relations testifies to periodical activity of giant lowfrequency steep spectrum radio sources.